Benign or Malign? A Syndrome of Acquired Hyperopia with Choroidal Folds. - Au, Michael (Optometry & Visual Performance, 2017)
Acquired hyperopia with choroidal folds is a benign syndrome characterized by flattening of the posterior pole in the affected eye, enlargement of the optic nerve complex, and the presence of a perineural space. The mechanisms responsible for these findings remain unclear, although choroidal folds have a number of possible etiologies, ranging from benign causes to malignant intraorbital masses. The proper workup is therefore critical to determine and to manage underlying pathologies. This case report presents a patient workup and management with unilateral acquired hyperopia and choroidal folds. Case Summary: A 26-year-old female presented with intermittent diplopia of increasing frequency in January 2013. In 2011, she was diagnosed with convergence insufficiency and unexplained partial hearing loss. A family history of hearing loss secondary to tumor growth prompted recommendations of yearly MRI studies. Upon refraction, retinoscopy yielded a hyperopic shift of +2.00D in the left eye compared to an examination two years prior. Fundus examination showed subtle radiations extending temporally from the optic nerve and concentrically from the macula. An OCT study revealed slight elevation nasal to the macula, with folds seen in the retinal layers. A referral was made for neuro-ophthalmic evaluation to rule out the presence of a mass. The patient received an MRI and was diagnosed with a benign syndrome of hyperopia with choroidal folds. Conclusion: Although choroidal folds can appear in the company of benign and idiopathic causes, this case report illustrates the need for thorough workup to rule out underlying pathology, as they can be potentially ominous. Moreover, it is also necessary to differentiate between functional and organic causes of diplopia before considering treatment with prism or vision therapy. Having been cleared of pathology, the patient was enrolled in vision therapy for treatment of convergence insufficiency.